2005
DOI: 10.1093/annonc/mdi064
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of HER-2 in gastric carcinoma: association with Topoisomerase IIα gene amplification, intestinal type, poor prognosis and sensitivity to trastuzumab

Abstract: HER-2/neu amplification is common in the intestinal type of gastric carcinoma, and it is associated with a poor outcome. HER-2 might be a useful target in this disease, and this hypothesis deserves to be investigated in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

47
472
4
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(527 citation statements)
references
References 16 publications
47
472
4
4
Order By: Relevance
“…These findings clearly show that CD90 potentially has a value as a target for immunotherapy. ERBB2 amplification is found in 20-30% of gastric carcinomas and is reported to be significantly associated with shorter survival of cancer patients (Tanner et al, 2005;Yano et al, 2006;Marx et al, 2009). How ERBB2 signaling affects tumor growth, invasion and metastasis is still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings clearly show that CD90 potentially has a value as a target for immunotherapy. ERBB2 amplification is found in 20-30% of gastric carcinomas and is reported to be significantly associated with shorter survival of cancer patients (Tanner et al, 2005;Yano et al, 2006;Marx et al, 2009). How ERBB2 signaling affects tumor growth, invasion and metastasis is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The ERBB2 (HER2) gene is amplified in approximately 20-30% of human breast and gastric cancers, in which it is associated with aggressive disease and early development of metastasis (Slamon et al, 1989;Tanner et al, 2005;Yano et al, 2006). A significant correlation between ERBB2 overexpression and expression of the stem cell marker ALDH1 has been found in a series of 491 breast cancer patients (Ginestier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] ErbB2 amplification or overexpression also seems to be associated with poorer prognosis, more aggressive disease and shorter survival in gastric cancer. [5][6][7] Preclinical and clinical studies of upper gastrointestinal adenocarcinomas, 2 and in particular, the large ToGA trial, which included adenocarcinomas of the stomach and gastro-oesophageal junction, have demonstrated that trastuzumab exerts antitumour activity on ErbB2-overexpressing tumours. 8 Most recently, this has led to the approval of the addition of trastuzumab to fluoropyrimidine/platinum-based therapies for patients with ErbB2-positive advanced gastric cancer by the European Medicines Agency (EMEA), the FDA and Health Canada.…”
mentioning
confidence: 99%
“…Her2-neu over expression in GA has been reported to range from 11.7% [14] to 23% [15] in different studies. Only some studies have documented Her2-neu protein overexpression or gene amplification to be associated with a worse prognosis [16] however larger studies could not confirm this as an independent prognostic factor [17,18]. Her2-neu prognostic significance is further minimized by its reported loss in approximately one third of patients when treated with trastuzumab, leading to drug resistance.…”
Section: Discussionmentioning
confidence: 99%